UPAYA PENINGKATAN HASIL BELAJAR LARI SPRINT MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING - Sepdeni Irian; Putra Muhammad Yusuf; Sri Erny Muliyani (Universitas Pendidikan Mandalika, 2021)
Based on the search results in the physical and physical education value list book, especially athletic learning for class V sprint running numbers at Embung Karung Elementary School in 2021, it was found that student learning outcomes were low. The goal to be achieved in this research is to be more effective in using the problem based learning model in order to improve the learning outcomes of sprint running in fifth grade students of SDN Rembang Karung in 2021. This research is a type of Classroom Action Research (CAR). The research sample used purposive sampling technique, amounting to 20 people. The implementation of this research was carried out collaboratively between researchers and physical education teachers at SDN Embung Karung with the application of the CAR cycle. The results of the study can be concluded that the problem based learning model can improve the learning outcomes of sprint running in fifth grade students of SDN Rembang Karung in 2021. This is evident from the mastery of learning which always increases significantly from cycle I to cycle II